A Pengaruh Penempatan Pegawai, Lingkungan Kerja dan Stres Kerja Terhadap Kinerja Pegawai Pada Kantor Dinas Penanaman Modal dan Pelayanan Tepadu Satu Pintu Kab. Luwu: Pengaruh Penempatan Pegawai, Lingkungan Kerja dan Stres Kerja Terhadap Kinerja Pegawai Pada Kantor Dinas Penanaman Modal dan Pelayanan Tepadu Satu Pintu Kab. Luwu - Nurwinda azis; Mus, Abdul Rahman; Alam, Syamsu (AkMen JURNAL ILMIAH, 2024)
This research was conducted with the aim of: Knowing and analyzing the effect of employee placement, work environment and work stress on the performance of employees of the Investment and One-Stop Integrated Service Office of Luwu Regency. This study used primary data through a survey of 85 employees as a sample of all employees, the survey was conducted from August to September 2023. Data analysis using multiple linear regression. Assisted with SPSS 24. The results showed that: (1) Employee placement has a significant effect on the performance of employees of the Kab. Luwu. (2) The work environment has a significant effect on the performance of employees of the Office of Investment and One-Stop Integrated Services of Luwu Regency. (3) Job Stress has a significant effect on the Office of Capital Investment and One-Stop Integrated Services Kab. Luwu.